If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -20 + x = 0 Reorder the terms: -20 + x + x = 0 Combine like terms: x + x = 2x -20 + 2x = 0 Solving -20 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 2x = 0 + 20 Combine like terms: -20 + 20 = 0 0 + 2x = 0 + 20 2x = 0 + 20 Combine like terms: 0 + 20 = 20 2x = 20 Divide each side by '2'. x = 10 Simplifying x = 10
| 695=13(k+5)+32 | | logx=0.45 | | 7b=85 | | 10(g-836)=740 | | 5x-5(-6-2x)=0 | | 5-7x=2x+8 | | 2-2y-3y=0 | | 9x-(3x+3)=4x-49 | | -2=6-x | | 29=2+3g | | 8(4w+9)=-8 | | 4x^2-11x+15=0 | | 9r+8s-5(8r-5s)= | | 3x^2+12x-24=-26 | | 1/3x^2-1/12x-1/6=0 | | 803=792-b | | -6(q-81)=-30 | | 4.3(4+2x)-4.2=13 | | 2(8x+4)=22x | | -10(s+5)=-101 | | Ln(5/x)=-2 | | k^2-4k-2=0 | | 9x+8y-5(8x-5y)= | | 3(s+11)+22=76 | | 4(3p+1)=64 | | Tan(60)=x/9 | | Lm(5/x)=-2 | | 4(z-66)-97=-33 | | 8=7-2x+2x | | 9(5x-8+7)6-3=42 | | 9(n-90)=45 | | 96=6(f+4) |